Overview Of Malaria Diagnosis Methods At South Minahasa District Community Health Center - Chrislie E. Ilat; Victor D. Pijoh; Janno B. B. Bernadus (Jurnal EduHealth, 2025)
Malaria remains a public health problem in Indonesia, including in South Minahasa Regency. Malaria diagnosis at primary healthcare facilities is crucial to support effective disease control and treatment. Objective: To describe the diagnostic methods for malaria in primary healthcare in South Minahasa Regency. Methods: This research is a descriptive study with a cross-sectional design. The sampling technique employed total sampling, involving 11 Community Health Centers that met the inclusion and exclusion criteria. Results: The results revealed that out of the 58 identified malaria cases, 81% were diagnosed using Rapid Diagnostic Tests (RDTs), while 19% were diagnosed through microscopic examination. In conclusion, this study indicates that RDT is more commonly used than microscopic examination.